2019
DOI: 10.3389/fmicb.2019.01001
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Coxsackievirus A4 Isolates From Hand, Foot, and Mouth Disease Cases in Shandong, China

Abstract: Coxsackievirus A4 (CVA4) is one of the most prevalent pathogens associated with hand, foot and mouth disease (HFMD), an acute febrile illness in children, and is also associated with acute localized exanthema, myocarditis, hepatitis and pancreatitis. Despite this, limited CVA4 genome sequences are currently available. Herein, complete genome sequences from CVA4 strains ( n = 21), isolated from patients with HFMD in Shandong province, China between 2014 and 2016, were determined and phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Several studies have shown that mutations in structural proteins have an effect on virulence and pathogenicity. Even one amino acid change in structural proteins may modulate important functions in virus infection [ 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that mutations in structural proteins have an effect on virulence and pathogenicity. Even one amino acid change in structural proteins may modulate important functions in virus infection [ 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to 2009, viral pathogens associated with HFMD included enterovirus A71 (EVA71) and CVA16; however, in recent years, other types of enteroviruses (EVs), such as CVA4, CVA6 and CVA10 have increased in prevalence [2–3]. Numerous outbreaks of CVA4 have occurred during recent years in different regions in China, such as Fujian [4], Shandong [5, 6], Sichuan [7], Yunnan [8], and Jiangsu [9]. Other countries, such as Thailand [2, 10], Australia [11] and Italy [12] have also reported CVA4 infections.…”
Section: Introductionmentioning
confidence: 99%
“…When using the neighbor-joining, minimum evolution and an UPGMA methods, the phylogenetic trees all formed almost the same topologies as the ML tree ( Supplementary Figure S1 ). This finding is rare among enteroviruses, as the prototype strain is always the most divergent strain among the genotyping results [ 3 , 4 , 5 , 6 , 7 , 8 ]. The 24 Chinese strains fell into the three genotypes, C, D and E, suggesting that the circulation of CV-A8 in China had distinctive evolutionary routes.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic trees based on the complete VP1 capsid sequences of EVs have been used for discrimination of genotypes, as the VP1 region is surface exposed, contains many important neutralisation epitopes and is serotype specific. Based on this approach, several EV serotypes, such as EV-A71, CV-A16, CV-A6, CV-A4, and CV-A2, have been genotyped [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%